The Role of Tax Law and Tax Sanctions on the Level of Taxpayer Compliance - Samsiah Samsiah (Review of International Economic, Taxation, and Regulations, 2025)
Taxpayer compliance remains a critical determinant of national revenue performance, yet persistent gaps between regulatory provisions and their actual enforcement continue to constrain optimal tax collection. The purpose of this study is to examine the influence of tax regulations and tax sanctions on taxpayer compliance. Compliance among taxpayers is a key factor for increasing national revenue derived from taxation. In reality, however, compliance has not yet reached optimal levels. Tax regulations serve as a legal basis that outlines taxpayer duties and rights, while tax sanctions function as a controlling tool that fosters compliance through fear of punishment. A quantitative research method was adopted, featuring both descriptive and verificative elements. Data came from questionnaires distributed to taxpayers and were subjected to statistical analysis. According to the results, tax regulations and tax sanctions together produce a positive and meaningful effect on compliance. This finding suggests that improved knowledge and enforcement of tax rules, combined with rigorous penalties, correspond with higher compliance rates. To conclude, well defined tax laws and properly functioning sanctions are highly important for raising taxpayer compliance. Consequently, the government needs to strengthen the dissemination of tax information and enforce sanctions consistently, thereby creating a taxation system that is both fair and optimal.